Oakeshott on Science as a Mode of Experience - Kaldis, Byron (Zygon, 2009)
Abstract. I offer a critical exposition and reconstruction of Michael Oakeshott's views on natural science. The principal aim is to enrich Oakeshott's modal schema by throwing light on it in terms of its internal consistency and by bringing to bear on it recent developments in philosophy in general and the philosophy of science in particular. The discussion brings out the special place reserved for philosophy, the crucial tenet of the separateness of these modes seen as Leibnizian monads as well as the special status allowed to science. It considers the possibility of combining one moment of philosophical thinking, namely ethics, with science in the midst of such modal separateness. I first offer a general introduction of how to approach Oakeshott's views on science. The next section stresses philosophy and its relation to science. This is followed by an elaboration of what the modes of experience are meant to be and how science is placed among them. An examination of Oakeshott's more particular views on science concludes the essay.